(untitled) (Kriminalističke teme, 2007)
Money laundering is the process of legalizing illegally obtained property. Initial activities aimed at combating this phenomenon correlate with the beginnings of an intensive campaign called "the war on drugs" at the international level. That was the period when money laundering was perceived as an activity connected with the legalization of property originally obtained by illegal production and trade of drugs. This paper uses official data on the situation in Bosnia and Herzegovina related to fictitious companies mainly founded with aim of tax evasions. Further it explains that profits from these activities were laundered through the banking system which had just started to implement standards of client's identification and suspicious transaction reporting. Trends in prosecution of money laundering at State Court of B&H show inadequacies in the seizure and confiscation of illegally obtained property.